H5N1 highly pathogenic influenza in Altaysky krai in 2014: causes and eradication - M. S. Volkov; A. V. Varkentin; V. N. Irza; A. S. Starova (Ветеринария сегодня)
Most of HPAI cases are associated with the periods of birds' migration to wintering and nesting areas. The last H5N1 cases in Russia were caused by virus introduction into backyards with hunting trophies (Primorsky Krai, 2008; Altay-sky Krai, 2014). The said cases prove the indisputable role of migrating wild birds in influenza virus circulation and spread maintenance. Today the only effective way to protect commercial poultry farms is a strict compliance with the biosecurity rules for closed poultry farms. Speaking about the threat ofavian influenza introduction the most vulnerable sectors are small farms and backyards where free ranged poultry is kept. The paper presents the analysis of H5 HPAI outbreak causes in the territory of the Altaysky Krai in 2014and eradication activities.